Fabrication methods of tissue engineering scaffolds - Correlo, V. M. (2014)
Scaffolds for tissue engineering are devices exploiting specific and complex physical and biological functions,in vitroorin vivo, communicating through biochemical and physical signals with cells and, when implanted, with the body environment. Scaffolds can be produced with several materials, most of them of synthetic origin, with an increasing interests on the use of biological or nature-derived materials. In most cases fabrication technologies are derived from already well-established industrial processes, with some new specific technologies having been developed in the last years to address required complexities. Often, a generalist approach is followed for the translation of materials and technologies designed for other applications, without considering the specific role of the scaffold from a physical and biological point of view. The book illustrates the scaffolds design principles with particular relevance to the biological requirements needed to control and drive the biological cross-talk, and reviews materials and fabrication and validation methods. The book is mainly addressed to graduate and post-graduate students, who are approaching tissue engineering or experienced researchers who wish to have condensed but comprehensive information on materials, fabrication techniques, biological principles, and design criteria. The contributors are among the scientific leaders in their respective fields.